Sistem Monitoring Postur Tubuh Lansia berbasis Wearable Embedded System dan Metode Klasifikasi Naive Bayes - Cahyanita Qolby Rahmarta Rizaputri; Dahnial Syauqy; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Posture is a movement made by humans, either standing, walking, face down, sitting or lyiing down. Movement of the body is also a process that requires complex integration of the limbs. Walkiing is the same as moving and both require balance control in the body. Posture will change with age and several factors are considered. The older you get, the more prone your body will be to injury. The Elderly Posture Monitoring System Based on the Wearable Embedded System and the Naive Bayes Classification Method was created to monitor the movement of an elderly person, usiing several determined axis points. The goal is to get a value from the angle of the body at the top and bottom. The installation of the point axis is at the top of the right and left calves and on the back as the main axis. This system uses the Naive Bayes classification method with 65 training data taken from 5 people and divided into 5 classes. In the test, it has obtained an error percentage of 10% to 20% and got an overall success with an accuracy percentage of 90% which was tested 10 times. The system will also send an Alert to the telegram bot if it occurs due to rapid changes from one class to another with a time frame that is limited to 10 seconds